2018
DOI: 10.1007/s10924-018-1256-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Ductility of Poly(Lactic Acid)/Poly(Butylene Adipate-co-Terephthalate) Blends Through Co-continuous Phase Morphology

Abstract: This paper examines the effect of the melt viscosities of the two component polymers on the morphology and mechanical properties of a series of biodegradable polymer blends. Melt blended compounds of poly(lactic acid) (PLA) and poly(butylene adipate-co-terephthalate) (PBAT) are prepared and their melt viscosities, thermal properties, crystallinity, mechanical properties and phase morphology are investigated. From the relative melt viscosities of PLA and PBAT in the processing regime used in the study, it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 34 publications
12
76
0
Order By: Relevance
“…The increase of elongation at break with the incorporation of PBAT into PLA blends, had been reported by some authors [36,42]. They have found that upon the addition of 20% PBAT to PLA/PBAT blends, there was an increase in the percentage of elongation at break of 26.6% [39] and 257% [33].…”
Section: Mechanical Propertiesmentioning
confidence: 58%
See 2 more Smart Citations
“…The increase of elongation at break with the incorporation of PBAT into PLA blends, had been reported by some authors [36,42]. They have found that upon the addition of 20% PBAT to PLA/PBAT blends, there was an increase in the percentage of elongation at break of 26.6% [39] and 257% [33].…”
Section: Mechanical Propertiesmentioning
confidence: 58%
“…Related to the percentage of crystallinity, in Table 5, this percentage is approximately the same for all samples. For the homopolymers, PLA100 and PBAT100 had a similar percentage of crystallinity as demonstrated by other authors [36,71]. Samples for DSC were taken from the compressed plaques, which were previously subjected to a thermal process.…”
Section: Compoundmentioning
confidence: 58%
See 1 more Smart Citation
“…Figure 3 (b) and 3 (c) indicate that the distance between particles is closer, thus will likely form co-continuous phase. The sample at the composition of 20/80 PBAT/PLA has a fine structure with the PBAT well dispersed in the PLA as also displayed by (Deng et al 2018). They have predicted that a co-continuous phase structure should be formed at a PBAT concentration of 19 wt%.…”
Section: Resultsmentioning
confidence: 94%
“…Besides, the distance between the particles also essential. (Deng et al 2018) has reported that when PBAT content less than 20 wt%, the PBAT disperses in PLA as droplets as can be seen in figure 3(a). However, when the PBAT content more than 20 wt%, PBAT and PLA form a co-continuous phase.…”
Section: Resultsmentioning
confidence: 95%